PENGENDALIAN MUTU BETON PADA PELAKSANAAN JALAN DENGAN PERKERASAN KAKU - Sutanto, Sutanto (Universitas Diponegoro, 2013)
Abstract Concrete as a building material has advantages compared with other materials because of its strength, easy to shape as desired designer, easy to work, easy to obtain raw materials, densities, treatment is relatively simple and economical considerations. As a material for rigid pavement on the highway project, treatment is similar to other construction work. Failure to avoid a construction that needs to be done according to standard and quality control requirements in SNI-03-1734-1989 on the concrete and SNI-03-1737-1989 on the highway as well as the international consensus as ASTM, ACI, etc.. Quality control includes the preparation of concrete materials, mixing, transporting, placing and casting the mixture, compacting the mixture, treatment and final concrete work. Specimen testing performed to evaluate the quality of the work. Of this evaluation will be concluded whether the work is in accordance with the plan. Â Key word : Concrete, rigid pavement Â